Profile of the Utilization of Natural Medicines as Complementary Therapy for Hypertension Patients in Lempuing Village, Bengkulu City - Avrilya Iqoranny Susilo; Reysa Pradifta (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Hypertension is one of the chronic diseases that requires long-term management. In addition to medical treatment, the use of natural medicine as a complementary therapy is widely chosen by the public because it is considered more natural and has minimal side effects. The study purpose was, to find out the Description of the Use of Natural Medicines as complementary therapy in hypertensive patients in Lempuing Village, Bengkulu City. Materials and methods, Descriptive research method, quantitative approach and observation design to describe the pattern of using natural medicine as complementary therapy in hypertension patients in the village of Bengkulu city and the determination of sample size using the total sampling method with a total sampling number of 88 samples. Results. From the study obtained the distribution of female-dominated patient characteristics as many as 65 samples (73.9%) then based on the age of the patient dominated by the age group of 56 years and above as many as 27 patients (30.7%). The types of natural ingredients used as medicine are 14 samples of bay leaves (15,9%) and 14 samples of turmeric (15,9%). The use of this natural medicine is based on hereditary habits and public belief in the effectiveness of natural ingredients. Conclusions. The use of natural medicines as complementary therapy in hypertensive patients is quite high in the village of lempuing. Sustainable education is needed so that people can use natural medicines wisely and according to recommendations.